2016
DOI: 10.1111/gcb.13459
|View full text |Cite
|
Sign up to set email alerts
|

Global patterns in lake ecosystem responses to warming based on the temperature dependence of metabolism

Abstract: Climate warming is expected to have large effects on ecosystems in part due to the temperature dependence of metabolism. The responses of metabolic rates to climate warming may be greatest in the tropics and at low elevations because mean temperatures are warmer there and metabolic rates respond exponentially to temperature (with exponents >1). However, if warming rates are sufficiently fast in higher latitude/elevation lakes, metabolic rate responses to warming may still be greater there even though metabolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
89
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(96 citation statements)
references
References 59 publications
(105 reference statements)
6
89
1
Order By: Relevance
“…Potential mechanisms behind this variation include acclimatization and adaptation processes, which are hypothesized to induce reduced temperature sensitivity with increasing average temperature (Atkin and Tjoelker ; Hikosaka et al ; Hartley et al ; Angilletta ; Smith and Dukes ). In this study, we found no evidence for a systematic change in activation energy with average temperature (Supporting Information S4 Table 2), which is in line with Perkins et al (), who reported consistent Q10 temperature coefficient values for ER regardless of the thermal history or community composition of biofilms, as well as with a global survey of activation energies based on satellite data by Kraemer et al ().…”
Section: Discussionsupporting
confidence: 92%
“…Potential mechanisms behind this variation include acclimatization and adaptation processes, which are hypothesized to induce reduced temperature sensitivity with increasing average temperature (Atkin and Tjoelker ; Hikosaka et al ; Hartley et al ; Angilletta ; Smith and Dukes ). In this study, we found no evidence for a systematic change in activation energy with average temperature (Supporting Information S4 Table 2), which is in line with Perkins et al (), who reported consistent Q10 temperature coefficient values for ER regardless of the thermal history or community composition of biofilms, as well as with a global survey of activation energies based on satellite data by Kraemer et al ().…”
Section: Discussionsupporting
confidence: 92%
“…Oxygen, lake temperature and water transparency also regulate predator-prey interactions through the vertical distribution and migration of phytoplankton and zooplankton and thereby modify the availability of refugia from predation (e.g., [90][91][92]). Further, a compressed or non-existent hypolimnion, due to a deeper thermocline and increasingly hypoxic conditions, will have costly energetic consequences for cooland cold-water fishes [93]. However, the opposite pattern could emerge in lakes with increasing hypolimnetic volume, assuming ample deepwater oxygen concentrations.…”
Section: Ecological Implicationsmentioning
confidence: 99%
“…Climate change has already impacted lakes and reservoirs in heterogeneous ways (McCullough et al, ) as cross‐scale interactions (Soranno et al, ) between climate and lake‐specific characteristics have caused some lake water temperatures to increase faster than air temperature and other lake water temperatures to cool despite increased air temperature (O'Reilly et al, ; Rose et al, ). These lake‐specific changes in water temperature impact organismal metabolic rates, with heterotrophy more sensitive to changes in temperature than autotrophy (Kraemer et al, ; Yvon‐Durocher et al, ). Watershed inputs of C and nutrients are also likely to change with predicted changes in precipitation.…”
Section: Introductionmentioning
confidence: 99%